1974
DOI: 10.1083/jcb.63.2.492
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction of Cationic Liposomes Containing Entrapped Horseradish Peroxidase With Cells in Culture

Abstract: Cationic liposomes composed of sphingomyelin, cholesterol, and stearylamine were prepared with horseradish peroxidase trapped inside. Stable particles were formed in which 10-12% of the enzymic activity appeared to be located at, or near, the outer surface of the liposome. Adsorption and uptake of liposomes by HeLa cells were followed cytochemically by electron microscopy and quantitated by enzyme assay and by the distribution and fate of particles labeled with [t4C]cholesterol and [lZSI]horseradish peroxidase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
25
0

Year Published

1975
1975
2000
2000

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(28 citation statements)
references
References 24 publications
3
25
0
Order By: Relevance
“…While this paper was in preparation, a study on the interaction of cationic liposomes containing horseradish peroxidase with cells in culture was reported by Magee et al (6). They reported that "liposomes containing horseradish peroxidase were adsorbed by HeLa cells at least 300 times as effectively as was free horseradish peroxidase".…”
Section: I17mentioning
confidence: 99%
“…While this paper was in preparation, a study on the interaction of cationic liposomes containing horseradish peroxidase with cells in culture was reported by Magee et al (6). They reported that "liposomes containing horseradish peroxidase were adsorbed by HeLa cells at least 300 times as effectively as was free horseradish peroxidase".…”
Section: I17mentioning
confidence: 99%
“…Recent work in this (1)(2)(3) and other laboratories (4)(5)(6)(7) has shown that mammalian cells cultured in vitro can incorporate large numbers of lipid vesicles, so-called liposomes, without significant cytotoxicity. Since a variety of water-soluble materials can be trapped inside vesicles (3)(4)(5)(6)(7)(8) and various glycolipids and glycoproteins inserted into the vesicle wall (3,8), uptake of vesicles of defined composition by cells offers a potential method for modifying cellular composition and for introducing nonpermeable, biologically active molecules into cells.…”
mentioning
confidence: 99%
“…Since a variety of water-soluble materials can be trapped inside vesicles (3)(4)(5)(6)(7)(8) and various glycolipids and glycoproteins inserted into the vesicle wall (3,8), uptake of vesicles of defined composition by cells offers a potential method for modifying cellular composition and for introducing nonpermeable, biologically active molecules into cells. The use of vesicles as "carriers" to enhance incorporation of cyclic nucleotides (1,2), enzymes (3,6), sugars (3,4), and anti-tumor drugs (3,4) into cultured cells has already been demonstrated.…”
mentioning
confidence: 99%
“…Liposomes are also under intensive investigation as vehicles for introducing membrane-impermeant substances (e.g., drugs, enzymes, chelating agents) into cells (2)(3)(4). Less attention has been devoted to the kinetics of vesicle-cell interaction, although a number of attempts have been made to define the mechanisms involved (5)(6)(7)(8)(9)(10).…”
mentioning
confidence: 99%